2022
DOI: 10.3390/genes13101817
|View full text |Cite
|
Sign up to set email alerts
|

KAT2A/E2F1 Promotes Cell Proliferation and Migration via Upregulating the Expression of UBE2C in Pan-Cancer

Abstract: Various studies have shown that lysine acetyltransferase 2A (KAT2A), E2F transcription factor 1 (E2F1), and ubiquitin conjugating enzyme E2 C (UBE2C) genes regulated the proliferation and migration of tumor cells through regulating the cell cycle. However, there is a lack of in-depth and systematic research on their mechanisms of action. This study analyzed The Cancer Genome Atlas (TCGA) to screen potential candidate genes and the regulation network of KAT2A and E2F1 complex in pan-cancer. Quantitative real-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 71 publications
(74 reference statements)
0
10
0
Order By: Relevance
“…E2F1 has been reckoned as a tumor-promoting gene. From one pan-cancer analysis, the KAT2A/E2F1 complex promotes cell proliferation and metastasis by upregulating the UBE2C expression ( Lin et al, 2022 ). An in SARC, the role of E2F1 has already been widely explored.…”
Section: Discussionmentioning
confidence: 99%
“…E2F1 has been reckoned as a tumor-promoting gene. From one pan-cancer analysis, the KAT2A/E2F1 complex promotes cell proliferation and metastasis by upregulating the UBE2C expression ( Lin et al, 2022 ). An in SARC, the role of E2F1 has already been widely explored.…”
Section: Discussionmentioning
confidence: 99%
“…Both HAT inhibitors as well as HDAC inhibitors have been suggested as potent therapeutic options in preclinical models and clinical trials for various cancers, including CRC (49). Furthermore, it has been demonstrated that KAT2A expression is elevated in CRC, and the knockdown of KAT2A has been shown to reduce the proliferation and migration of CRC cell lines (11,50).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, KAT2A upregulation associates with worse patient outcomes in several cancers, including breast, lung, colon, and renal cancers [ 55 , 56 , 57 , 58 ]. KAT2A contributes to cancer through the control of transcriptional activity, mainly the co-activation of E2F and Myc transcriptional targets [ 59 ]. In renal cancer, KAT2A promotes tumor growth and accelerates the metastatic phenotype of cancer cells by regulating glycolytic metabolism through MCT1 upregulation [ 60 ].…”
Section: Several Brd Family Members Play a Fundamental Role In Cancer...mentioning
confidence: 99%